1977
DOI: 10.1111/j.1365-2133.1977.tb14249.x
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical distribution of sunlight

Abstract: The relative distribution of natural ultraviolet radiation has been measured at ten sites on the surface of an unclothed manikin for 2 h around solar noon on 19 different days during late summer in Canterbury, U.K. The dosimeter used was polysulphone film. The results obtained indicate that vertical surfaces of the body receive about one half of the dose relative to the vertex and that the relative doses at different sites are independent of weather conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 12 publications
0
34
0
2
Order By: Relevance
“…For the shoulder, these range from 0.18 to 0.45, compared to ranges of 0.68 to 0.80 (Diffey et al, 1977), 0.89 to 0.99 (Gies et al, 1988) and 0.66 to 0.70 (Holman et al, 1983) for exposures in full sun. Similarly, for the chest, the range is 0.14 to 0.32, compared to 0.58 to 0.73 (Diffey et al, 1977), 0.42 to 0.58 (Gies et al, 1988) and 0.44 to 0.46 (Holman et al, 1983). The ratios for the human body sites in the shade of the tree are lower than those without the protection of the shade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the shoulder, these range from 0.18 to 0.45, compared to ranges of 0.68 to 0.80 (Diffey et al, 1977), 0.89 to 0.99 (Gies et al, 1988) and 0.66 to 0.70 (Holman et al, 1983) for exposures in full sun. Similarly, for the chest, the range is 0.14 to 0.32, compared to 0.58 to 0.73 (Diffey et al, 1977), 0.42 to 0.58 (Gies et al, 1988) and 0.44 to 0.46 (Holman et al, 1983). The ratios for the human body sites in the shade of the tree are lower than those without the protection of the shade.…”
Section: Discussionmentioning
confidence: 99%
“…Manikin and head form studies have been previously employed to measure the erythemal exposure to various anatomical body sites on the face (Wong et al, 1992;Diffey et al, 1977;Gies et al, 1988;Holman et al, 1983). Airey et al, (1995) found that various human activities may be simulated for erythemal exposure measurements by tilting the headform to various angles.…”
Section: Introductionmentioning
confidence: 99%
“…Sun exposure recordings on a whole-body manikin in Canterbury for 1 h either side of solar noon showed that the hands and upper arms received higher doses than some parts of the face. 81 The rarity of BCC on the hands and forearms, therefore, appeared not to be due simply to lack of exposure of these sites.…”
Section: Anatomic Site Distributionmentioning
confidence: 94%
“…Exposure ratios for predominantly upright postures have been measured (for example, [6,9,10]). Annual solar UV exposures have been calculated using these exposure ratios.…”
Section: Introductionmentioning
confidence: 99%